Analisis Fungsi, Kategori, dan Peran Sintaksis dalam Teks Deskripsi Buku Bahasa Indonesia Kelas VII Kurikulum Merdeka - Ika Rizki Refima Putri; Juni Us’ariasih; Firda Rubiyanti Desvika Sari; Fora Shaffilia Hakiki; Asep Purwo Yudi Utomo; Riskiana Widi Astuti (Pusat Riset dan Inovasi Nasional, 2024)
Syntactic analysis isn’t only used for the use of structural grammar, but also for explaining the relationship or connection between functions, categories, and roles in the syntactic structure to achieve a correct sentence structure. The purpose of this study is to describe the function, structure, and role of syntax in Bahasa Indonesia Kelas VII Kurikulum Merdeka book. This type of research is included in a qualitative approach with a qualitative descriptive design. The method used in this study is the agih method using reading and note-taking techniques, while the method of presenting data using informal data presentation. The data used is the descriptive text from the Bahasa Indonesia Kelas VII Kurikulum Merdeka book. The results of this study found 30 sentences with various sentence patterns from 4 samples of descriptive text with the most frequently found details being S-P-O syntactic functions, noun-verb-noun syntax categories, and actor-activity-target syntactic roles. Through this research it is hoped that it can provide benefits to readers so that they can deepen their knowledge in the field of syntax, and can be used as reference material and references for further research that is in line with this research.